Improving lipophilicity of 5-(1-acetyl-5-phenylpyrazolidin-3-ylidene)-1, 3-dimethylbarbituric acid increases its efficacy to activate hypoxia-inducible factors. (1st November 2022) - Sonoda, Kento; Ujike, Saki; Katayama, Akito; Suzuki, Norio; Kawaguchi, Shin-ichi; Tsujita, Tadayuki
Graphical abstract: Abstract: Hypoxia-inducible factor (HIF) activators aid the treatment of renal anemia and ischemia. Recently, PyrzA (5-(1-acetyl-5-phenylpyrazolidin-3-ylidene)-1, 3-dimethylbarbituric acid), a HIF activator by PHD inhibition without a 2-oxoglutarate moiety was reported. However, PyrzA has low lipophilicity, and it was necessary to improve its solubility by synthesizing derivatives. In this study, we synthesized and evaluated a higher lipophilic derivative of PyrzA and found that it exhibited higher HIF activity and stabilizing ability at low concentrations compared to Roxadustat, a commercially available HIF activator.